Multi-stage inhibition in breast cancer metastasis by orally active triple conjugate, LHTD4 (low molecular weight heparin-taurocholate-tetrameric deoxycholate) - Alam, Farzana; Al-Hilal, Taslim A.; Park, Jooho; Choi, Jeong Uk; Mahmud, Foyez; Jeong, Jee-Heon; Kim, In-San; Kim, Sang Yoon; Hwang, Seung Rim; Byun, Youngro (ELSEVIER SCI LTD, 2016)
Targeting multiple stages in metastatic breast cancer is one of the effective ways to inhibit metastatic progression. To target human metastatic breast cancer as well as improving patient compliance, we developed an orally active low molecular weight heparin (LMWH)-taurocholate conjugated with tetrameric deoxycholic acid, namely LHTD4, which followed by physical complexation with a synthetic bile acid enhancer, DCK. In breast cancer, both transforming growth factor-beta 1 (TGF-beta 1) and CXCL12 exhibit enhanced metastatic activity during the initiation and progression stages of breast cancer, thus we direct the focus on investigating the antimetastatic effect of LHTD4/DCK complex by targeting TGF-beta 1 and CXCL12. Computer simulation study and SPR analysis were performed for the binding confirmation of LHTD4 with TGF-beta 1 and CXCL12. We carried out in vitro phosphorylation assays of the consecutive receptors of TGF-beta 1 and CXCL12 (TGF-beta 1R1 and CXCR4, respectively). Effects of LHTD4 on in vitro cell migration (induced by TGF-beta 1) and chemotaxis (mediated by CXCL12) were investigated. The in vivo anti-metastatic effect of LHTD4 was evaluated in an accelerated metastasis model and an orthotopic MDA-MB-231 breast cancer model. The obtained K-D values of TGF-beta 1 and CXCL12 with LHTD4 were 0.85 and 0.019 mu M respectively. The simulation study showed that binding affinities of LHTD4 fragment with either TGF-beta 1 or CXCL12 through additional electrostatic interaction was more stable than that of LMWH fragment. In vitro phosphorylation assays of TGF-beta 1 and CXCR4 showed that the effective inhibition of receptor phosphorylation was observed with the treatment of LHTD4. The expressions of epithelial to mesenchymal transition (EMT) marker proteins such as vimentin and Snail were prevented by LTHD4 treatment in in vitro studies with TGF-beta 1 treated MDA-MB-231 cells. Moreover, we observed that LHTD4 negatively regulated the functions of TGF-beta 1 and CXCL12 on migration and invasion of breast cancer cell. In several advanced orthotopic and experimental breast cancer metastasis murine models, the treatment with LHTD4 (5 mg/kg daily, p.o.) significantly inhibited metastasis compared to the control. Overall, LHTD4 exhibited anti-metastatic effects by inhibiting TGF-beta 1 and CXCL12, and the clinically relevant dose of orally active LHTD4 was found to be effective in preclinical studies without any apparent toxicity. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: TGF-BETA; ANGIOGENESIS; BINDING; DELIVERY; DOCKING; TUMORS; ROLES